2013
DOI: 10.1096/fj.13-233965
|View full text |Cite
|
Sign up to set email alerts
|

De novo generation of infectious prions with bacterially expressed recombinant prion protein

Abstract: The prion hypothesis is strongly supported by the fact that prion infectivity and the pathogenic conformer of prion protein (PrP) are simultaneously propagated in vitro by the serial protein misfolding cyclic amplification (sPMCA). However, due to sPMCA's enormous amplification power, whether an infectious prion can be formed de novo with bacterially expressed recombinant PrP (rPrP) remains to be satisfactorily resolved. To address this question, we performed unseeded sPMCA with rPrP in a laboratory that has n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 48 publications
(81 reference statements)
2
52
0
Order By: Relevance
“…In light of these observations, the authors suggested that the GPI anchor of PrP Sc has little or no role in either the propagation or infectivity of prion agents. The finding that prion infectivity does not require the GPI anchor is consistent with observations by several groups, including Chesebro and others mentioned above (98,184,188,189). Importantly, however, the de novo generation of prion infectivity can be achieved with rPrP alone.…”
Section: Effect Of the Gpi Anchor On Prp Sc Infectivitysupporting
confidence: 90%
See 1 more Smart Citation
“…In light of these observations, the authors suggested that the GPI anchor of PrP Sc has little or no role in either the propagation or infectivity of prion agents. The finding that prion infectivity does not require the GPI anchor is consistent with observations by several groups, including Chesebro and others mentioned above (98,184,188,189). Importantly, however, the de novo generation of prion infectivity can be achieved with rPrP alone.…”
Section: Effect Of the Gpi Anchor On Prp Sc Infectivitysupporting
confidence: 90%
“…Several recent studies have, indeed, generated transmissible prion diseases with rPrP in natural hosts (96,97,100,189,(191)(192)(193)(194). These infectious recombinant prions were generated with or without the application of serial PMCA (sPMCA) (96,97,99,100,189,(191)(192)(193)(194)(195)(196)(197)(198).…”
Section: De Novo Generation Of Prions With Recombinant Prion Proteinmentioning
confidence: 99%
“…However, the PrP Sc amplified through PMCA performed using phosphatidylethanolamine alone did not preserve the prion strain characteristics of the input PrP Sc (53). Synthetic phospholipids and RNA induced the spontaneous generation of two types of prions in Escherichia coli recPrP-based PMCA, and their prion strain characteristics appeared to be unchanged during the serial amplification (8,54,55). Our study suggests that polyanions such as GAGs and nucleic acids were essential for accurate in vitro replication of prions in PMCA performed using Bac-PrP.…”
Section: Identification Of the Binding Regions Of Prpmentioning
confidence: 99%
“…Another promising approach is based on the development of techniques that allow for the efficient production of PrP Sc from recombinant sources in vitro. [67][68][69] H/D exchange in combination with mass spectrometry 70 or solid-state NMR spectroscopy 71 should be able to provide structural information on a local level complementary to the data available by electron microscopy. Prions were found to escape the selection pressure of antiprion compounds in vivo through the selection of drug-resistant, structural variants.…”
Section: Future Approachesmentioning
confidence: 99%